Thyroxine Levels in the Nephrotic Syndrome - Ariyanto Harsono; Sardjito Djojohadipringgo; I. Nyoman Yardana (Paediatrica Indonesiana, 1982)
Thirteen children, seven boys and six girls aged between 3 to 12 years wit/1the diagnosis of Nephrotic Syndrome were assessed for clinical and laboratoryfigns with special attention on T 4 levels.In the first examination, done during the full blown illness, T4 levels rangedbetween 1 ug % to 10 ug % (mean: 5.4 + 3.14 ug %).In remission the levels were significantly elevated, ranges between 3.6 ug % to 18.6 ug% rmean: 11.6 + 5.34 ug %).Meanwhile, the observation of serum albumine and globuline concentrations showed a significantly rise ( p<0.005).Comparison with the results of other investigators have also been discussed.